2022
DOI: 10.1027/1016-9040/a000449
|View full text |Cite
|
Sign up to set email alerts
|

School Does Not Kill Creativity

Abstract: Abstract. Based on meta-analyses, intervention studies, and investigations outside of the creativity literature, this paper makes seven evidence-informed propositions about the relationships between creativity and school functioning. First, creative abilities are drivers, not brakes of school achievement. Second, the negative attitudes toward creative students sometimes observed in schools usually concern a small and particular group of creative students: those who are most impulsive and nonconforming. Third, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 102 publications
1
10
0
Order By: Relevance
“…For example, Hargrove and Nietfeld (2015) found that practicing metacognitive strategies increased metacognitive knowledge and regulation and subsequently led to more creative outcomes. But in line with recent research (Karwowski, 2021; Mevarech & Paz‐Baruch, 2022; Pesout & Nietfeld, 2021; Sidi et al., 2020; Urban et al., 2021; Urban & Urban, 2021; Zielińska et al., 2021, 2022), the present study provides openings for more complex interventions, such as those that can target all four facets of self‐regulation: namely cognitive strategies, metacognitive knowledge at the Person level (when, why, and how one can perform creatively), metacognitive regulation at Task × Person level (planning, accurately monitoring and evaluating one's creative performance), intrinsic motivation at the Person level (performing creatively because I feel confident at doing so and because I recognize the value of creativity), intrinsic motivation at Task × Person level (monitoring and regulating my interest during task resolution), and affective states on both Person and Task × Person level.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…For example, Hargrove and Nietfeld (2015) found that practicing metacognitive strategies increased metacognitive knowledge and regulation and subsequently led to more creative outcomes. But in line with recent research (Karwowski, 2021; Mevarech & Paz‐Baruch, 2022; Pesout & Nietfeld, 2021; Sidi et al., 2020; Urban et al., 2021; Urban & Urban, 2021; Zielińska et al., 2021, 2022), the present study provides openings for more complex interventions, such as those that can target all four facets of self‐regulation: namely cognitive strategies, metacognitive knowledge at the Person level (when, why, and how one can perform creatively), metacognitive regulation at Task × Person level (planning, accurately monitoring and evaluating one's creative performance), intrinsic motivation at the Person level (performing creatively because I feel confident at doing so and because I recognize the value of creativity), intrinsic motivation at Task × Person level (monitoring and regulating my interest during task resolution), and affective states on both Person and Task × Person level.…”
Section: Discussionsupporting
confidence: 88%
“…Metacognitive knowledge and motivation at the Person level, along with metacognitive monitoring and regulation of cognitive strategies, affect, and motivation regulation at the Task × Person level, are the four key facets of the ability to self‐regulate one's actions in different contexts (Efklides, 2008, 2011). Since Pesut (1990) suggested that general metacognitive awareness is helpful for the production of creative ideas, a growing number of studies have focused on the role of metacognitive knowledge (Urban et al., 2021), accurate metacognitive regulation skills (Mevarech & Paz‐Baruch, 2022; Pesout & Nietfeld, 2021; Sidi et al., 2020; Steele et al., 2021; Urban & Urban, 2021), and overall self‐regulation (Karwowski, 2021; Zielińska et al., 2021, 2022) in creative performance. Pesut's (1990) view is supported by Urban et al.…”
Section: Discussionmentioning
confidence: 99%
“…Mindfulness implies an unjudgmental awareness of the present and requires a conscious break from the automatic mental processes of cognitive evaluation (e.g., good and bad, useful and useless; Shen et al, 2021). In order to gain insight into an object and put forward new ideas and solutions, it is necessary to examine the object objectively and calmly and avoid relying on previous empirical assumptions (Karwowski, 2021). Breaking previous assumptions and building new knowledge means a certain degree of creativity.…”
Section: Mindfulness and Creativitymentioning
confidence: 99%
“…The temptation to focus on the individual attributes of 'bad teachers' is strong enough to override most attempts to consider more structural or systematic failings of the educational system [41]. Bad teaching is also discussed in terms of the many ways in which teachers can stifle students' creativity, despite the concept of schools 'killing' creativity being vastly overestimated [42]. Better communication of ongoing creativity research, from work being conducted on education to articulating the nuances of negative or malevolent creativity, can help dispel some of the myths.…”
Section: Positive Creativity In Educationmentioning
confidence: 99%